(untitled) (Journal of NELTA, 2018)
The present paper reports a study that aimed to explore secondary school (SS) English language (EL) teachers’ present practices of and perceived needs for continuing professional development (CPD) in Bangladesh. In 21st century worldwide educational settings, ‘change’ is the only constant trend. Consequently, EL teachers need to be continuously updated in their professional knowledge base and skills. They must be engaged in effective CPDs to keep abreast of innovations in language learning and teaching for their own career development and better learning outcomes for learners. Using a semi-structured questionnaire qualitative data was collected from 10 secondary EL teachers. The findings show that overall scenario of SS EL teachers’ CPD is not encouraging. The paper also discusses some implications for teachers’ professional learning. Journal of NELTA, Vol 22 No. 1-2, December 2017, Page: 1-12